Ignorance Implicatures and Non-doxastic Attitude Verbs - Blumberg, Kyle (Proceedings of the Amsterdam Colloquium, 2025)
This paper is about conjunctions and disjunctions in the scope of non-doxastic attitude verbs. These constructions generate a certain type of ignorance implicature. I argue that the best way to account for these implicatures is by appealing to a notion of contextual redundancy (Schlenker, 2008; Fox, 2008; Mayr and Romoli, 2016). This pragmatic approach to ignorance implicatures is contrasted with a semantic account of disjunctions under ‘wonder’ that appeals to exhaustification (Roelofsen and Uegaki, 2016). I argue that exhaustification-based theories cannot handle embedded conjunctions, so a pragmatic account of ignorance implicatures is superior.